Biogas production potential from goat droppings at varying operating conditions - Sharma, Smika; Pandey, Rajeev; Shrestha, Poushan; Thapa, Rajan; Lohani, Sunil Prasad (Journal of Innovations in Engineering Education, 2025)
This paper investigates the biogas production potential of goat droppings under ambient and controlled temperature conditions and discusses the prospects of biogas production potential from goat droppings in Nepal. Different batches of experiments under varied total solids (TS) percentages and temperature conditions indicated that the biogas yield of goat droppings is 558 L/kg VSadded and 522 L/kgVSadded under controlled temperature conditions of 30°C at 10% and 8% TS, respectively. However, under ambient conditions in summer (average temperature 24°C), biogas yield drops to 221 L/kgVS and 143 L/kgVS at 10% and 8% TS, respectively. Inconsistent biogas production was observed at ambient conditions during winter (average temperature 10oC) with very low biogas yield of 13 and 8 L/kgVS at 8% and 10% TS, respectively. The theoretical estimation of total biogas production potential from 14 million goats in 2022 for the controlled temperature, summer, and winter was estimated to be 136.82 million m3/year, 54.34 million m3/year, and 1.86 million m3/year, respectively. The result could pave the way forward for relevant stakeholders to prepare relevant strategies for possibilities to enhance digester temperature in winter and utilizing goat droppings together with livestock manure and other organic waste in the country.